Effect of biaxial cyclic tension on the fatigue life and damage mechanisms of Cr–Mo steel. (June 2016) - Gaur, Vidit; Doquet, Véronique; Persent, Emmanuel; Roguet, Eléonore
Highlights: Cyclic biaxial tension tests were run at various biaxialities on 2.5%Cr–1%Mo steel. Moderate biaxialities ( B = 0.25 and 0.5) had a beneficial effect on fatigue lives. By contrast equibiaxial tension slightly reduced the fatigue lives. Various endurance criteria failed to capture both mean stress and biaxiality effects. An alternative fatigue criterion extending Gerber's parabola was proposed. Abstract: Combined cyclic tension and internal pressure tests with various proportions of each loading were run on a 2.5%Cr–1%Mo steel to investigate the effect of positive stress biaxiality on fatigue lives and damage mechanisms. While moderate stress biaxiality had a beneficial effect on fatigue lives, attributed mainly to a retardation of crack initiation, equibiaxial tension had a slightly detrimental effect, attributed to a "pseudo size effect". Intergranular facets associated with temper and hydrogen embrittlement were observed on the fracture surfaces. The evolutions of their surface fraction with Δ K and load biaxiality suggested a possible reduction in crack growth rate at moderate biaxialities. Several popular multiaxial fatigue criteria failed to describe all fatigue data. Thus, a new fatigue criterion based on Gerber's parabola has been proposed. It captures the evolution of the endurance limit under the combined effects of a positive mean stress and positive biaxiality.